Optimization of radio frequency components of cryogenic nuclear magnetic resonance spectroscopy system : doctoral thesis - Kolar, Petar (P. Kolar ; Fakulty of electrical engineering and computing, 2020)
Nuclear magnetic resonance (NMR) is a physical phenomenon used to study materials by recording the interaction of radiofrequency (RF) electromagnetic radiations with the nuclei placed in a strong magnetic field. The spectroscopic technique, used to observe local magnetic fields around atomic nuclei, is called NMR spectroscopy. Modern NMR spectroscopy measurements, especially in condensed matter physics, have a trend of continuous decrease of magnitude of receiving signals, which is a problem because, as response signal levels decrease, the background noise of the used NMR spectroscopy systems gradually becomes a bigger problem. Indeed, the assurance of high measuring sensitivity is one of the most challenging issues for any NMR spectroscopy system today. In this thesis, an accurate noise model of the entire probe-to-spectrometer receiving chain for condensed matter physics is proposed. It is based on the concept of noise figure. The model predicts both the signal and noise levels in every component of the NMR spectroscopy receiving chain. Furthermore, it enables identification of the "weakest" component and, therefore, the optimization of the whole system. The most important property of the proposed model is the possibility to find system parameters that reduce the measurement time by an a priori calculation, rather than an a posteriori approach. The model was tested experimentally by NMR measurements on several different samples. It was found that the measurement time can still be significantly shortened, down to at least one half of the measurement time, starting from optimized conditions with commercially available components. Thus, the proposed model can be used as a tool for both quantitative analysis of the noise properties and a sensitivity prediction of practical NMR systems in physics and material science. A Python-written program, which calculates noise figure and predicts input and output signal-to-noise ratios (SNRs) of the NMR receiving chain, based on the described noise model of the receiving chain, has been created and made available online. Additionally, an electromagnetic model of the NMR probe, which predicts SNR level at its output, has been developed and presented in this thesis. This model has been compared to the proposed noise model of the receiving chain, and the comparison results showed to be satisfactory. Finally, two possible upgrades of NMR preamplifiers: one in terms of power gain level enhancement with the addition of a second stage amplifier, and the other in terms of a new proposed scheme, PCB layout and proper electronic components selection for the NMR preamplifier, have been proposed in order to further improve noise properties of the NMR spectroscopy system receiving chain. Keywords: NMR, noise, noise figure, preamplifier, measurement time decrease, sensitivity enhancement